Agricultural research and extension system in Nepal: An organizational review - Babu, Suresh Chandra; Sah, Ram Pratap (International Food Policy Research Institute, 2019)
This paper aims to address the status and challenges of agriculture research and extension and their linkages in Nepal. Agriculture plays a vital role in Nepal’s economy, employment, and livelihoods, contributing nearly 33 percent to gross domestic product, 66 percent to employment, and 50 percent to exports. Despite the government of Nepal’s (GON’s) priority and policy supports for more than two decades, the growth of agriculture has been very slow (less than 3.0 percent), mainly due to inadequate access to demand-driven technologies and extension services and to inputs, credits, markets, and incentives. Dynamic agriculture research and extension systems are instrumental for bringing transformations in agriculture.